Hemolymph profiling reveals post bleeding stress in Tachypleus gigas - John, Akbar; Sheikh, Hassan I (2019)
Horseshoe crabs amoebocyte cells degranulates to form a gel clot when in contact with endotoxins/Lipopolysaccharide (LPS) that are cellular constituents of gram-negative bacteria. This phenomenon is the basis of both Horseshoe crab immune system and detection of endotoxin in biologicals. Present study investigates the quality of amoebocyte cells in Tachypleus gigas pre and post bleeding under captivity. Wild and captive horseshoe crabs (5 months captivity) were bled in 6 anticoagulant formulations (A, B, C, D, E and F). Experiments were carried out in triplicate using a total of 18 T. gigas (3 crabs for each anticoagulant treatment) to determine cell viability and density. No profound difference in cell density observed between captive and wild crabs with the mean value of 1.1×107 cells/mL and 1.167×107 cells/mL, respectively. while, the cell viability of captive group was significantly lower than the wild crabs (P<0.001). Cell viability of captive group in anticoagulant A, B, C, D, E, F were 40%, 52%, 58%,11%, 18%, 39%, respectively. Whilst, cell viability of wild crabs were 80%, 84%, 86%, 36%, 45%, 54%, respectively. The anticoagulant formulations had varying capabilities in maintaining cell viability with formula B and C being significantly better than the rest (P<0.001), however, no significant difference between Formula B and C was noted. This was attributed to the various components in the anticoagulant formulations such as the buffering and chelating agent used. We conclude that the captivity has negative effect on the amoebocyte viability. Anticoagulant formulation is crucial to determine the hemolymph profiling of xiphosuran arthropods.